2015
DOI: 10.1111/iar.12099
|View full text |Cite
|
Sign up to set email alerts
|

Foldback reflectors near methane hydrate bottom‐simulating reflectors: Indicators of gas distribution from 3D seismic images in the eastern Nankai Trough

Abstract: Understanding of fluid behavior and gas distribution in the shallow subsurface are important considerations in gas hydrate formation and the global carbon cycle. Estimation of gas distribution based on reflection seismic surveys, however, is difficult because the boundary of a gas‐bearing zone is indistinct and not systematically defined. This study reports distinctive features related to gas‐hydrate distribution and possible fluid migration in high‐resolution 3D seismic‐reflection data from sediments of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
(101 reference statements)
1
4
0
Order By: Relevance
“…Velocity profiles inside the mud conduits and in the surrounding regions, whose domains are illustrated in red and gray dashed lines, are plotted in Figure . While the bottom simulation reflector (BSR) that manifests the base of the gas hydrate stability zone may be found here (shown in red triangles) as widely observed in the Nankai margin (e.g., Ashi et al, ; Ohde et al, ; Otsuka et al, ), it does not connect across the mud conduit of the studied mud volcano. (c) Example of root mean square (RMS) velocity spectra of the supergather of the neighboring 5 common midpoints in the central part of the mud conduit within the KK#3 mud volcano.…”
Section: Application To a Mud Volcano In The Nankai Margin Using Reflsupporting
confidence: 48%
“…Velocity profiles inside the mud conduits and in the surrounding regions, whose domains are illustrated in red and gray dashed lines, are plotted in Figure . While the bottom simulation reflector (BSR) that manifests the base of the gas hydrate stability zone may be found here (shown in red triangles) as widely observed in the Nankai margin (e.g., Ashi et al, ; Ohde et al, ; Otsuka et al, ), it does not connect across the mud conduit of the studied mud volcano. (c) Example of root mean square (RMS) velocity spectra of the supergather of the neighboring 5 common midpoints in the central part of the mud conduit within the KK#3 mud volcano.…”
Section: Application To a Mud Volcano In The Nankai Margin Using Reflsupporting
confidence: 48%
“…This large error can be produced by picking error in seismic reflection images (Marcaillou et al 2006 ) and by the discrepancy between the true value and the adopted value of the P-wave velocity, as well as the thermal conductivity of the sediment (Ganguly et al 2000 ; Henrys et al 2003 ). Neither double BSRs (Foucher et al 2002 ; Chhun et al 2017 ) nor foldback reflectors (Otsuka et al 2015 ) were found in the survey lines used for our study, preventing errors in the calculation of the heat flow from the BSRs due to misinterpretation of the BSRs.…”
Section: Methodsmentioning
confidence: 77%
“…Therefore, the values calculated from the BSRs can be used to estimate the geothermal regime up to approximately 1 km below the seafloor. Moreover, because the presence of BSRs in the Nankai subduction zone has been widely confirmed (Ashi et al 2002 ; Baba and Yamada 2004 ; Otsuka et al 2015 ), heat flow values can be calculated over wide areas when physical properties, such as seismic velocity, density, and thermal resistance, are estimated from seismic surveys and deep-sea drilling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of gas appears in seismic data as reductions in acoustic impedance, which strengthens the reflectivity coefficient and results in either HARs, a polarity change, or as anomalous low velocity, low coherency zone [79][80][81]. Other seismic indicators of gas-charged fluids include flat spots, bright spots, and dim spots, which are each known as "direct hydrocarbon indicators", and are thus important features to look for when searching for hydrocarbons in marine sediments [50,82].…”
Section: Seismic Evidence For Gas Source and Migration Pathways Into mentioning
confidence: 99%